Transmitting the Spirit : Religious Conversion, Media, and Urban Violence in Brazil - Oosterbaan, Martijn, 1975- (Book collections on Project MUSE., 2017)
"Examines Pentecostalism, media, society, and culture in the turbulent favelas of Brazil. Explores both the evolving role of religion in Latin America and the proliferation of religious ideas and practices in the postmodern world"--Provided by publisher